Group A streptococci induce stronger M protein-fibronectin interaction when specific human antibodies are bound - Wrighton, Sebastian; Ahnlide, Vibha Kumra; André, Oscar; Bahnan, Wael; Nordenfelt, Pontus (Frontiers in Microbiology, 2023)
Group A streptococcus (GAS) is a highly adapted, human-specific pathogen that is known to manipulate the immune system through various mechanisms. GAS’ M protein constitutes a primary target of the immune system due to its spatial configuration and dominance on the bacterial surface. Antibody responses targeting the M protein have been shown to favor the conserved C region. Such antibodies (Abs) circumvent antigenic escape and efficiently bind to various M types. The ability of GAS to bind to fibronectin (Fn), a high molecular weight glycoprotein of the extracellular matrix, has long been known to be essential for the pathogen’s evolutionary success and fitness. However, some strains lack the ability to efficiently bind Fn. Instead, they have been found to additionally bind Fn via the A-B domains of their M proteins. Here, we show that human Abs can induce increased Fn-binding affinity in M proteins, likely by enhancing the weak A-B domain binding. We found that this enhanced Fn binding leads to a reduction in Ab-mediated phagocytosis, indicating that this constitutes a GAS immune escape mechanism. We could show that the Fc domain of Abs is necessary to trigger this phenomenon and that Ab flexibility may also play a key role. We, moreover, saw that our Abs could enhance Fn binding in 3 out of 5 emm type strains tested, belonging to different clades, making it likely that this is a more generalizable phenomenon. Together our results suggest a novel synergistic interplay of GAS and host proteins which ultimately benefits the bacterium.